Kenya : Fourth Review Under the Three-Year Arrangement Under the Extended Credit Facility, Request for a Waiver and Modification of Performance Criteria: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Kenya. (IMF Staff Country Reports; Country Report ;, 2012)
The staff report for the fourth review under the three-year arrangement under the Extended Credit Facility, request for a waiver and modification of performance criteria, prepared by a staff team of the IMF, following discussions that ended on September 25, 2012, with the officials of Kenya on economic developments and policies. Based on information available at the time of these discussions, the staff report was completed on October 15, 2012. The views expressed in the staff report are those of the staff team and do not necessarily reflect the views of the Executive Board of the IMF.